IMPLEMENTASI SISTEM KREDIT SEMESTER DALAM MEMAKSIMALKAN KEMAMPUAN BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Mia Wati; Rosichin Mansur; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Semester Credit System is an educational innovation that aims to provide full facilities and services to student’s learning abilities so that the potential possessed by students can be maximally developed. The existence of the Semester Credit System makes students motivated to complete their education in a time appropriate to their learning abilities. Students who can complete all their learning obligations quickly can complete education in 4 semesters (2 years). Unlike the acceleration class, Semester Credit System has heterogeneous services where in a class there are various study groups with different facilities and services. Researchers conduct research related to the implementation of the Semester Credit System, especially in learning Islamic Education. The focus of research is related to learning planning, learning implementation, and assessment systems based on Semester Credit Systems. Researchers use a qualitative approach to the type of case study research. The data collection techniques use interviews, observation, and documentation. In its implementation, the teacher has an innovation related to learning planning and applies it in the learning process and then conducts an assessment with certain codes to assess all student learning activities that include affective, cognitive, and psychomotor.